SIKAP DAN FAKTOR-FAKTOR YANG MEMENGARUHI PEMBELIAN KONSUMEN TERHADAP ROTI KAMURA BAKERY DI KOTA BANDAR LAMPUNG - Ria Devita; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Lampung University, 2021)
This study aims to analyze the attitude of consumers toward the purchase of Kamura Bakery bread in Bandar Lampung City, the purchase pattern, and the factors that influence the number of bread purchased. This research was conducted at Kamura Bakery Sukarame branch in Bandar Lampung City. The research method is a survey with accidental sampling technique. Respondents were 60 Kamura Bakery consumers who had bought/consumed Kamura Bakery at least once in the last one month. The research data are analyzed using Fishbein Multi-attribute analysis, descriptive statistics, and multiple linier regression analysis. Data collection was conducted in June - July 2020. The results showed that the consumers bought bread at Kamura Bakery mostly because of the taste. The highest amount of Kamura Bakery’s bread purchased was chocolate flavor, the average number purchased was 28 pieces per household monthly, and the average frequency was seven times a month. The price of sweetened condensed milk and household income have a significantly negative effects on the number of purchase, while the number of family members has a significant positive effect on the number of bread purchased. Key words: bread, consumer attitude, purchasing factors, purchasing patterns